2018
DOI: 10.1371/journal.pone.0202559
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inadequate access to healthcare services on emergency room visits. A comparison between physical and mental health conditions

Abstract: This paper estimates the influence of inadequate access to healthcare services on the rate of Emergency Room (ER) hospital visits in Australia. We take micro-data on different types of healthcare shortfalls from the 2012 Australian Survey of Disability, Aging and Carers, and employ Propensity Score Matching (PSM) techniques to identify their effects on ER visits. We find that shortfalls in access to various medical services increases ER visits for individuals with mental and physical conditions by about the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…For example, between 2003 and 2011 in the UK, it has been observed that while the diagnosis of anxiety among young people in general practice has remained constant, the reporting of symptoms has increased . It has been suggested that a reduced stigma associated with mental illness has led to an increase in help‐seeking behaviour …”
Section: Discussionmentioning
confidence: 99%
“…For example, between 2003 and 2011 in the UK, it has been observed that while the diagnosis of anxiety among young people in general practice has remained constant, the reporting of symptoms has increased . It has been suggested that a reduced stigma associated with mental illness has led to an increase in help‐seeking behaviour …”
Section: Discussionmentioning
confidence: 99%
“…Extensive research shows that increased availability and accessibility to a GP or after-hours services are associated with significant decreases in ED utilisation (Kraaijvanger et al, 2016;Lowthian et al, 2011;Vecchio, Davies, & Rohde, 2018). A study conducted in NZ by Thornton, Fogarty, Jones, Ragaban, & Simpson (2014) out of Middlemore Hospital looked at the motives behind non-urgent patients (within the Australasian triage scale categories of 3, 4, and 5) self-referring to Middlemore Hospital ED rather than accessing a primary healthcare service.…”
Section: Availabilitymentioning
confidence: 99%
“…Short consultation length may be assisting the misconception that GPs cannot manage complex conditions. Patients with non-urgent health conditions may decide to substitute inaccessible GP services with the ED, even though primary care does have the provisions to manage patients within the Australasian triage scale 3 -5 (Thornton, 2014;Vecchio, Davies & Rohde, 2018).…”
Section: Dissatisfaction With General Practitionermentioning
confidence: 99%
See 1 more Smart Citation
“…Disparities in access to healthcare can lead to delays in, or non-receipt of, appropriate care ( Lindly, Zuckerman, & Kuhlthau, 2019 ); higher financial burden on the patient ( Drainoni et al, 2006 ); increased use of emergency care ( Brousseau, Bergholte, & Gorelick, 2004 ); higher hospitalisation rates ( Long, Coughlin, & Kendall, 2002 ); higher risk for, and poor management of, chronic illness or comorbid conditions ( Bowles, Naylor, & Foust, 2002 ); greater risk of unmet needs ( Coughlin, Long, & Kendall, 2002 ) and increased burden and cost on the healthcare system due to preventable disease exacerbations and premature deaths ( Vecchio, Davies, & Rohde, 2018 ). Ready access to healthcare on the other hand, is linked to a variety of important outcomes including better health status ( Nicolaidis et al, 2013 ), higher patient satisfaction ( Batbaatar, Dorjdagva, Luvsannyam, Savino, & Amenta, 2017 ), lower hospitalisation rates ( Ansari, Laditka, & Laditka, 2006 ), and reduced burden and cost on the healthcare system ( Reid et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%